2017
DOI: 10.1039/c7tb01556a
|View full text |Cite
|
Sign up to set email alerts
|

Sustained subconjunctival delivery of cyclosporine A using thermogelling polymers for glaucoma filtration surgery

Abstract: We successfully developed a subconjunctival delivery system of CsA using an injectable thermogel to inhibit post-surgical scar formation after glaucoma filtration surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…Biodegradable hydrogels are typically soft materials and have been used in multiple biomedical applications, [1][2][3][4] such as tissue engineering scaffolds and drug delivery carriers. They can include biodegradable components such as poly(lactic acid) (PLA), 5 poly(e-caprolactone) (PCL), 6 poly(D,L-lactide-co-glycolide) (PLGA), 7 and poly(e-caprolactone-co-lactide) (PCLA) 8 as hydrophobic blocks copolymerized with hydrophilic components such as poly(ethylene glycol) (PEG). Among the various classes of hydrogels developed, the copolymers of poly(L-lactide)-copolyethyleneglycol-co-poly(L-lactide) (PLLA-PEG-PLLA) and their derivatives show promising potential in a number of biomedical applications, for example, with materials designed to form stable self-assembling micellar structures 9 with the hydrophobic core allowing good loading of hydrophobic drugs, while also undergoing biodegradation.…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable hydrogels are typically soft materials and have been used in multiple biomedical applications, [1][2][3][4] such as tissue engineering scaffolds and drug delivery carriers. They can include biodegradable components such as poly(lactic acid) (PLA), 5 poly(e-caprolactone) (PCL), 6 poly(D,L-lactide-co-glycolide) (PLGA), 7 and poly(e-caprolactone-co-lactide) (PCLA) 8 as hydrophobic blocks copolymerized with hydrophilic components such as poly(ethylene glycol) (PEG). Among the various classes of hydrogels developed, the copolymers of poly(L-lactide)-copolyethyleneglycol-co-poly(L-lactide) (PLLA-PEG-PLLA) and their derivatives show promising potential in a number of biomedical applications, for example, with materials designed to form stable self-assembling micellar structures 9 with the hydrophobic core allowing good loading of hydrophobic drugs, while also undergoing biodegradation.…”
Section: Introductionmentioning
confidence: 99%
“…This is because that the cumulative release percent is the ratio of the drug release amount to loading amount. Although the release amount increases, the drug loading amount becomes larger and the ratio of them decreases (Gong et al., 2009; Luo et al., 2016; Sun et al., 2017). Previous studies also indicated that the drug release from the biodegradable hydrogel due to both the drug diffused from the porous structure of hydrogel and the polymer degradation (Tang et al., 2008; Xie et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the restricted permeability and fast clearance of drugs induced by the complex anatomy and physiology of the eye [29]. For example, a delivery system for dexamethasone (DEX), a hydrophobic glucocorticoid, was investigated for the treatment of posterior segment diseases by Zhang et al [30]; a delivery system for cyclosporine A (CsA), an effective immunosuppressive agent, was investigated for the inhibition of postoperative scarring after filtration surgery for glaucoma by Sun et al [31]; and a co-delivery system for metformin (MET), a potential agent for inhibiting neovascularization, and levofloxacin (LFH), a hydrophobic antibiotic for treating ocular infections and inflammatory responses, was investigated for the treatment of corneal neovascularization (CNV) by Liu et al [32]. In addition, the excellent biocompatibility of PLGA-PEG-PLGA hydrogels and their capability as an ophthalmic drug delivery system were confirmed by Chan et al [29].…”
Section: Applications Of Thermoresponsive Hydrogels Using Block Copolmentioning
confidence: 99%